1993
DOI: 10.1016/0020-7519(93)90061-3
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to ivermectin and pyrantel of Ancylostoma ceylanicum and Necator americanus

Abstract: AbStrBCt-BEHNKEJ.M., ROSE R. and GARSIDE P. 1993. Sensitivity to ivermectin and pyrantel of Ancylosioma ceylanicum and Necator americanus. International Journal for Parasitology 23: 945-952. Experiments were carried out in the hamster to compare the relative susceptibility of Necator americanus and Ancylostoma ceylunicum to treatment with ivermectin. A.ceylanicum was found to be 300 times more sensitive to the anthelmintic with a 50% effective dose (ED,,) of the order of lo-15pg kg-' body weight whilst that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
17
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
7
17
1
Order By: Relevance
“…Studies by Rajasekeriah et al (1989) also reported the relative insensitivity of N. americanus to IVM in the hamster model. The results of the above in vitro experiments in which the effects of IVM and pyrantel on motility were assessed support the results of these previous in vivo experiments (Behnke et al, 1993;Rajasekeriah et al, 1989) as A. ceylanicum and N. americanus were shown to have similar sensitivities to pyrantel, whereas A. ceylanicum was found to be approximately 50 times more sensitive to IVM (t = 3 h) than N. americanus. The difference in responsiveness to IVM does not appear to be related to response time as concentrations of IVM-PO4 that immobilized A. ceylunicum in 3 h (1.14 pm, 50% worms immobilized) had no detectable effect on N. americanus over 24 h.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Studies by Rajasekeriah et al (1989) also reported the relative insensitivity of N. americanus to IVM in the hamster model. The results of the above in vitro experiments in which the effects of IVM and pyrantel on motility were assessed support the results of these previous in vivo experiments (Behnke et al, 1993;Rajasekeriah et al, 1989) as A. ceylanicum and N. americanus were shown to have similar sensitivities to pyrantel, whereas A. ceylanicum was found to be approximately 50 times more sensitive to IVM (t = 3 h) than N. americanus. The difference in responsiveness to IVM does not appear to be related to response time as concentrations of IVM-PO4 that immobilized A. ceylunicum in 3 h (1.14 pm, 50% worms immobilized) had no detectable effect on N. americanus over 24 h.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies (Behnke et al, 1993) showed that in the hamster host, A. ceylanicum was on average 300 times more sensitive to IVM than N. americanus. Studies by Rajasekeriah et al (1989) also reported the relative insensitivity of N. americanus to IVM in the hamster model.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Unlike in C. elegans or C. oncophora (Cully et al, 1994;Njue et al, 2004), we could find no evidence of channels formed by, or incorporating, the GluCl␤ subunit of H. contortus. This suggests that the GluCl of different nematode species are rather different, supporting observations that ivermectin has varying effects on nematodes (Behnke et al, 1993;Sheriff et al, 2002;Holden-Dye and Walker, 2006). One factor contributing to the difference between the C. elegans and H. contortus GluCl␣3B channels might be that the amino acid residue at position 256 in C. elegans is phenylalanine rather than leucine, and the L256F change has been associated with resistance in C. oncophora.…”
Section: Discussionsupporting
confidence: 58%
“…Multiple studies investigating hookworm susceptibility to anthelmintics have reported that lower drug concentrations are effective against A. ceylanicum compared with N. americanus. 7,[38][39][40] These observations are supported by our comparative studies of the half-maximal inhibitory concentration (IC 50 ) values for ABZ and pyrantel pamoate (Table 4). For both compounds, higher IC 50 values were recorded for field isolates of hookworm compared with A. ceylanicum.…”
supporting
confidence: 71%